Bone health in chronic kidney disease‐mineral and bone disorder: a clinical case seminar and update. Issue 12 (5th December 2018) - Aleksova, Jasna; Ng, Kong W.; Jung, Caroline; Zeimer, Howard; Dwyer, Karen M.; Milat, Frances; MacIsaac, Richard J.
Abstract: The metabolic abnormalities affecting bone in the setting of chronic kidney disease (CKD) are complex with overlapping and interacting aetiologies and have challenging diagnostic and management strategies. Disturbances in calcium, phosphate, fibroblast growth factor 23, parathyroid hormone concentrations and vitamin D deficiency are commonly encountered and contribute to the clinical syndromes of bone disorders in CKD, including hyperparathyroidism, osteomalacia, osteoporosis and adynamic bone disease. Mineral and bone abnormalities may also persist or arise de novo post‐renal transplantation. The Kidney Disease Improving Global Outcomes organisation describes these mineral metabolism derangements and skeletal abnormalities as 'CKD Mineral and Bone Disorder'. Patients with this disorder have an increased risk of fracture, cardiovascular events and overall increased mortality. In light of the recently updated 2017 guidelines from the Kidney Disease Improving Global Outcomes, we present a clinical case‐based discussion to highlight the complexities of investigating and managing the bone health of patients with CKD with a focus on these updates.